De novo transcriptome profiling of cold-stressed siliques during pod filling stages in Indian mustard (Brassica juncea L.) - Sinha, Somya; Raxwal, Vivek K.; Joshi, Bharat; Jagannath, Arun; Katiyar-Agarwal, Surekha; Goel, Shailendra; Kumar, Amar; Agarwal, Manu (Frontiers in Plant Science, 2015)
Low temperature is a major abiotic stress that impedes plant growth and development. Brassica juncea is an economically important oil seed crop and is sensitive to freezing stress during pod filling subsequently leading to abortion of seeds. To understand the cold stress mediated global perturbations in gene expression, whole transcriptome of B. juncea siliques that were exposed to sub-optimal temperature was sequenced. Manually self-pollinated siliques at different stages of development were subjected to either short (6 h) or long (12 h) durations of chilling stress followed by construction of RNA-seq libraries and deep sequencing using Illumina’s NGS platform. De-novo assembly of B. juncea transcriptome resulted in 133641 transcripts, whose combined length was 117 Mb and N50 value was 1428 bp. We identified 13342 differentially regulated transcripts by pair-wise comparison of 18 transcriptome libraries. Hierarchical clustering of these differentially expressed transcripts along with Spearman correlation analysis identified two major clusters representing early (5-15 DAP) and late stages (20-30 DAP) of silique development. Detailed analysis led to the discovery of two gene expression clusters whose transcripts were inducible at both durations of the cold stress irrespective of the developmental stages. We further explored the expression patterns of gene families encoding for transcription factors (TFs), transcription regulators (TRs) and kinases, and found that cold stress induced protein kinases specifically during early silique development. We validated the digital gene expression profiles of selected transcripts by qPCR and found a high degree of concordance between the two analyses. To our knowledge this is the first report of transcriptome sequencing of cold-stressed B. juncea siliques. The data generated in this study would be a valuable resource for not only understanding the cold stress signaling pathway but also for introducing cold hardiness in B. juncea.